POPULASI BAKTERI, EFISIENSI PAKAN, PERTUMBUHAN DAN KELANGSUNGAN HIDUP IKAN NILA (Oreochromis Niloticus) YANG DIBERI PAKAN BERSINBIOTIK - Devi Craselly Sihombing; Ade Dwi Sasanti; Mohamad Amin (Universitas Sriwijaya, 2017)
ABSTRACTSynbiotics are a balanced combination of probiotics and prebiotics. Synbiotics indirectly influence the population of bacteria in the digestive tract and survival of the fish. The purpose of this research is to determine the affection of synbiotic addition to diet for population of intestinal bacteria, feed efficiency, survival rate and growth of tilapia. This research conducted on October-December 2016 at Laboratorium Budidaya Perairan, Departement of Aquaculture, Faculty of Agriculture, Sriwijaya. This research methode used Completly Randomize Design with six treatments and three replications. Tilapia feed treated with different dose of sweet potato extract prebiotics. P0 treatment by feeding (commercial pellets without probiotics and prebiotics), P1 treatment (5 ml probiotic + 2,5 ml prebiotic/kg pellets), P2 treatment (5 ml probiotic + 5,0 ml prebiotic/kg pellets), P3 treatment (5 ml probiotic + 7,5 ml prebiotic/kg pellets), P4 treatment (5 ml probiotic + 10 ml prebiotic/kg pellets) and P5 treatment (5 ml probiotic + 12,5 ml prebiotic/kg pellets). Parameters to be observed is population of intestinal bacteria, feed efficiency, growth and survival rate of tilapia. The highest value population of intestinal bacteria is P5 treatment with 4,17x104 cfu/ml. P3 treatment has the highest value of feed efficiency 50,19%, growth of length 1,92 cm, growth of weight 8,87 gram and survival rate 88,89%. Keywords: synbiotic, probiotic, prebiotic, feed.